(3QSGdI aj JMdjd GdJJf hGdbghIs - (3GdTGNhQj, GdHMQGfj, SdjeGf Hf Ydj Hf SdjeGf Hf QGTO Hf CHj XHjI, J (B1101(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj QRbfG ef WjHGJ GdQRb(B... (3hHYO agPg QSGdI hLjRI cJHJgG Ydi eG QCjJg eSWhQG aj HYV GdChQGb(B... (3aj JMQje GdJJf hbghI GdHf(B...s
(3BNQgG (B:s
(3aef jba Ydi ChGeQc hfhGgjc hjYed HcJGHc hSfI fHjc(B... (3hUdi Gddg eMeO hBdg GdWGgQjfhSde JSdjeG cKjQG eHGQcG HQMeJc jG CQMe GdQGMejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B794s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B794s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis